Conceptual design of the Kumgang laser: a high-power coherent beam combination laser using SC-SBS-PCMs towards a Dream laser. (2015) - Kong, Hong Jin; Park, Sangwoo; Cha, Seongwoo; Ahn, Heekyung; Lee, Hwihyeong; Oh, Jungsuk; Lee, Bong Ju; Choi, Soungwoong; Kim, Jom Sool
Abstract : In this review paper, we introduce a self-phase controlled stimulated Brillouin scattering phase conjugate mirror (SC-SBS-PCM) and the Kumgang laser. The SC-SBS-PCM was proposed and demonstrated its success at the academic low power level, 100 mJ@10 Hz . The Kumgang laser is under development to verify whether the SC-SBS-PCM is operable at the kW level. It is a 4 kW beam combination laser combining four 1 kW beams using the SC-SBS-PCM. If the Kumgang laser functions successfully, it will be the most important step towards a Dream laser, a hypothetical laser with unlimited power and a high repetition rate.